2023
DOI: 10.1007/s00432-023-04624-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Polo-like kinase 1 (PLK1) triggers cell apoptosis via ROS-caused mitochondrial dysfunction in colorectal carcinoma

Abstract: Colorectal cancer (CRC) is one of the most frequently diagnosed cancers. Polo-like kinase 1 (PLK1), a member of the serine/threonine kinase PLK family, is the most investigated and essential in the regulation of cell cycle progression, including chromosome segregation, centrosome maturation and cytokinesis. However, the nonmitotic role of PLK1 in CRC is poorly understood. In this study, we explored the tumorigenic effects of PLK1 and its potential as a therapeutic target in CRC. First, immunohistochemistry ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The reduction of PLK1 can lead to the accumulation of ROS and mitochondrial dysfunction in cancer cells. 30 Therefore, we measured ROS levels in A549 cells and found that treatment with 6 for 24 h caused a dosedependent increase in ROS (Figure 6C,D). As elevated ROS levels can result in oxidative stress, we found that the expression of oxidative stress-related genes, including ATF4, SESN2, G-CSF, and TRIB3, was significantly increased after the treatment with 6 (Figure 7A).…”
Section: ■ Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The reduction of PLK1 can lead to the accumulation of ROS and mitochondrial dysfunction in cancer cells. 30 Therefore, we measured ROS levels in A549 cells and found that treatment with 6 for 24 h caused a dosedependent increase in ROS (Figure 6C,D). As elevated ROS levels can result in oxidative stress, we found that the expression of oxidative stress-related genes, including ATF4, SESN2, G-CSF, and TRIB3, was significantly increased after the treatment with 6 (Figure 7A).…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…As shown in Figure B, PLK1 decreased sharply after 6 -treatment, further demonstrating the antiproliferation effect of 6 . The reduction of PLK1 can lead to the accumulation of ROS and mitochondrial dysfunction in cancer cells . Therefore, we measured ROS levels in A549 cells and found that treatment with 6 for 24 h caused a dose-dependent increase in ROS (Figure C,D).…”
Section: Resultsmentioning
confidence: 90%